Magnetization dating at a medieval monastery (Tupholme, Lincolnshire) - Borradaile, Graham John (Archaeometry, 1999)
Keywords: tupholme

The 'White Canons' Rediscovered: clearance work at Tupholme Abbey - Bainbridge, Norman (History Today, 1990)
Norman Bainbridge on springtime for Tupholme Abbey.
Keywords: tupholme

Field Survey of Site of Premonstratensian Abbey of Tupholme - Cocroft, W.; Wilson, P. (RCHME Archaeological Requests, 1989)
Keywords: tupholme

Tupholme Abbey - White, Andrew (Lincolnshire Museums Information Sheet, Archaeology Series, 1979)
Keywords: tupholme

Houses of Premonstratensian canons: The abbey of Tupholme - Page, William (A History of the County of Lincoln, 1906)
Keywords: tupholme